A preliminary evaluation of the impact that the COVID-19 pandemic could have on female employability in the tourism and hospitality sectors in Italy. Issue 2 (4th May 2021) - Mihailescu, Radu; Rinaldi, Azzurra
ABSTRACT: The article focuses on the analysis of preliminary data regarding the challenges that female employability in the tourism and hospitality sectors in Italy has faced and will continue to experience as a result of the economic impact of the COVID-19 lockdown. A review of the literature shows the precarious nature of the female employability opportunities that were already inherent in the industry. The research surveyed 54 male and female employees in the tourism and hospitality sectors regarding perceptions and expectations of work security and future job opportunities. The results revealed that no significant differences were found regarding job opportunity expectations between male and female respondents in general. The gaps in expectations became significant, however, when household, pressure obligations such as childcare, care of relatives or household duties are taken into consideration. These expectations seem to be less for the male respondents. These preliminary results suggest a need for governmental policies to aid in the provision of household support.